Photoinhibition: Physiological response of plants to high-irradiance stress. A review - Casierra-Posada, Fánor (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Light is essential for plant growth and development, but may be harmful in excess. Photoinhibition, defined as the inhibition of photosynthesis caused by excessive radiation, affects field production to a great extent. The exposure to additional stress factors during exposure to high levels of radiation increases the potential of photoinhibitory effects, so that inhibition of photosynthesis indicates that the plant is subjected to stressful conditions. Photoinhibition may be reversible, playing a protective role for the photosynthetic systems, but it can also reflect damage that has already occurred in the photosynthetic apparatus, which in this case, is irreversible. In this review, some physiological and molecular mechanisms of photoinhibition are presented and the interaction between light and other stress factors and their effects on plants are discussed.